Gitamahatmya! Paratexts in Miniature Bhagavad Gitas with Special Reference to Pictures and Gender - Skarpeid, Jon (Postscripts: The Journal of Sacred Texts, Cultural Histories, and Contemporary Contexts, 2019)
This article studies paratextuality - epigraphs, prefaces, illustrations etc. - in four miniature Bhagavad Gitas. The analysis focuses particular on format, illustrations and gender. In addition to Gérard Genette’s concept of paratexts, the theory includes Roland Barthes’ “Rhetoric of the image” and Ervin Goffman’s Gender Advertisements. The study shows that some publishers have prioritized readability while others have chosen smaller amuletic versions that are more difficult to read. The physical presence of the holy Gita is considered valuable in any case, and even the tiny editions are readable. With one exception, the world is to a large extent seen from a male perspective. However, the gender ideology is presented in a rather indirect way. In one publication, a gender and class hierarchy is reflected in a couple of illustrations. Two other publications have added mantras and ritual prescription that are hardly meant for women. One publisher have only included portions of the Bhagavad Gita, and stanzas where females are described as inferior to males as well as stanzas that explicitly address the four classes, are omitted.